Anonim "Epitafium Leandra, Izydora i Florentyny" (ICERV 272: "Epitaphium Leandri, Isidori et Florentine") - Krynicka, Tatiana (Vox Patrum, 2020)
"Epitaphium Leandri, Isidori et Florentine" (ICERV 272) translated into Polish and briefly commented.